Mechanisms responsible for F-actin stabilization after lysis of polymorphonuclear leukocytes (The Rockefeller University Press, 1992)
While actin polymerization and depolymerization are both essential for cell movement, few studies have focused on actin depolymerization. In vivo, depolymerization can occur exceedingly rapidly and in a spatially defined manner: the F-actin in the lamellipodia depolymerizes in 30 s after chemoattractant removal (Cassimeris, L., H. McNeill, and S. H. Zigmond. 1990. J. Cell Biol. 110:1067-1075). To begin to understand the regulation of F-actin depolymerization, we have examined F-actin depolymerization in lysates of polymorphonuclear leukocytes (PMNs). Surprisingly, much of the cell F-actin, measured with a TRITC- phalloidin-binding assay, was stable after lysis in a physiological salt buffer (0.15 M KCl): approximately 50% of the F-actin did not depolymerize even after 18 h. This stable F-actin included lamellar F- actin which could still be visualized one hour after lysis by staining with TRITC-phalloidin and by EM. We investigated the basis for this stability. In lysates with cell concentrations greater than 10(7) cells/ml, sufficient globular actin (G-actin) was present to result in a net increase in F-actin. However, the F-actin stability was not solely because of the presence of free G-actin since addition of DNase I to the lysate did not increase the F-actin loss. Nor did it appear to be because of barbed end capping factors since cell lysates provided sites for barbed end polymerization of exogenous added actin. The stable F-actin existed in a macromolecular complex that pelleted at low gravitational forces. Increasing the salt concentration of the lysis buffer decreased the amount of F-actin that pelleted at low gravitational forces and increased the amount of F-actin that depolymerized. Various actin-binding and cross-linking proteins such as tropomyosin, alpha-actinin, and actin-binding protein pelleted with the stable F-actin. In addition, we found that alpha-actinin, a filament cross-linking protein, inhibited the rate of pyrenyl F-actin depolymerization. These results suggested that actin cross-linking proteins may contribute to the stability of cellular actin after lysis. The activity of crosslinkers may be regulated in vivo to allow rapid turnover of lamellipodia F-actin.